Self-facilitation framework for developing soft skills – FSIAR. Issue 6 (10th October 2018) - Sethi, Deepa
Abstract : Purpose: The purpose of this paper is to evaluate various ways in which soft skills can be developed. It proposes a self-facilitation framework to develop and enhance soft skills. Design/methodology/approach: A survey questionnaire was developed based on a pilot study with reference to key components of an individual's life which can be instrumental in developing soft skills. Study was conducted on participants of Management Development Program (MDP) in a business school in India between June 2017 and March 2018. Participants who had attended a session on soft skills were selected for the study. In all, 180 participants from 12 programs filled the responses based on a five-point Likert scale. Of all, 167 responses were complete and deemed fit for analysis. Factor analysis using SPSS 22 resulted in five factors, namely, family, self, industry, academia, and resources. Findings: Findings indicated that irrespective of gender, age categories, type of organizations working in, and the years of work experience, majority respondents accepted that soft skills could be developed through a holistic approach with the help of a self-facilitation framework (FSIAR) comprising family, self, industry, academia, and resources. Research limitations/implications: The framework can be generalized by testing the questions with a larger number of respondents. A further research could be to delve into the cultural factors while using this framework in various countries. Practical implications: The study is extremely beneficial for heads of organizations, working executives, educational institutions, scholars, faculty, and trainers. Originality/value: This study for the first time has proposed a self-facilitation framework – FSIAR for developing and enhancing soft skills of an individual.